2007
DOI: 10.1159/000102953
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hypertension in Patients with Chronic Renal Failure

Abstract: Background: Many etiologies causing pulmonary hypertension (PH) have been reported, and one of the background disease seen with patients with PH is chronic renal failure (CRF); however, the pathogenesis of PH in this group of patients is not explained satisfactorily. Objectives: The aims of this study were to evaluate the incidence of unexplained PH among patients with CRF and to suggest possible etiologic factors. Methods: Two hundred and eleven patients with CRF were evaluated and the ones who have comorbid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
92
7
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(116 citation statements)
references
References 40 publications
12
92
7
4
Order By: Relevance
“…Additionally, the prevalence of PHT in the stage 1-4 CKD patients and stage 5 patients was similar. Studies on non-dialysis-dependent stage 5 CKD patients reported that the prevalence of PHT ranges from 9-39% and that the prevalence of PHT is higher in patients undergoing dialysis than in nondialysis patients (9)(10)(11)(12). In the present study the prevalence of PHT in patients with stage 5 CKD not undergoing HD was 58.3%, which is higher than reported earlier (9,11,13,14).…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations
“…Additionally, the prevalence of PHT in the stage 1-4 CKD patients and stage 5 patients was similar. Studies on non-dialysis-dependent stage 5 CKD patients reported that the prevalence of PHT ranges from 9-39% and that the prevalence of PHT is higher in patients undergoing dialysis than in nondialysis patients (9)(10)(11)(12). In the present study the prevalence of PHT in patients with stage 5 CKD not undergoing HD was 58.3%, which is higher than reported earlier (9,11,13,14).…”
Section: Discussioncontrasting
confidence: 62%
“…Accordingly, we think in addition to CKD patients undergoing HD early-stage CKD patients should also be considered high risk patients. In most studies on patients with CKD, sPAP has been estimated as Doppler-derived sPAP and various sPAP cut offs have been used, ranging from 25 to ≥45 mmHg (9,11,(13)(14)(15). In the present study sPAP ≥35 mmHg based on Doppler echocardiography was considered diagnostic for PHT and the high prevalence of PHT in this study may be explained due to the lack of uniformity in diagnostic criteria and sPAP cutoffs in the literature.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Our data, which include all classes of PH, reveal a higher proportion of CKD in those patients with PH (36% in this study versus 4% in REVEAL). Similarly, Havlucu et al (25) reported a PH prevalence rate of 39% (assessed using Doppler echocardiogram) among those patients with nondialysis-dependent CKD. Underlying muscle mass influences serum creatinine generation (and thus, eGFR), and patients with PH might have muscle wasting from chronic heart failure, thereby underestimating the kidney function.…”
Section: Discussionmentioning
confidence: 92%